Rancang Bangun Sistem Proteksi Pengisian Daya Pada Sepeda Listrik Roda Tiga Vokasi Unesa Terintegrasi Panel Surya - Yanuar Rahman; Ferly Isnomo Abdi; Warju Warju; Daeng Rahmatullah; Nur Vidia Laksmi B (CV. SINAR HOWUHOWU, 2026)
The increasing use of electric bicycles as an environmentally friendly mode of transportation has created a growing need for safe and efficient battery charging systems. One of the main challenges in battery charging systems is the risk of overcharging and overtemperature, which can reduce battery performance and lifespan. This study aims to design and develop a charging protection system for the UNESA Vocational three-wheeled electric bicycle integrated with a solar panel using an ESP32-based Auto Cut-Off method. The developed system utilizes a PZEM-017 voltage sensor, DHT22 and PT100 temperature sensors, and a Solid State Relay (SSR) as an automatic power disconnection actuator. The research employed an experimental method consisting of system design, hardware assembly, functional testing, data collection, and result analysis. Testing was conducted using voltage variations of 54.4 V, 57.6 V, and 60 V for Over Voltage Protection (OVP), and temperature variations of 25°C, 40°C, and 50°C for Over Temperature Protection (OTP). The results indicate that the system successfully detected overcharge and overtemperature conditions and automatically disconnected the charging process according to the predefined set points. The sensor measurement error was found to be less than 1% compared to reference measuring instruments. Furthermore, the hybrid charging system integrating solar panels and grid electricity achieved a remaining battery capacity of 60%, which was higher than the 45% remaining capacity obtained from grid-only charging under the same operating conditions. Therefore, the developed protection system effectively improves battery charging safety while supporting the utilization of renewable energy in three-wheeled electric bicycles.